2020
DOI: 10.1111/aje.12720
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of permit requests and issuance for regulated alien and invasive species in South Africa for the period 2015‐2018

Abstract: Invasive species typically establish in areas outside their natural distribution through accidental introduction and accidental release or escape. Some species are introduced legally for economic and social benefits such as recreational hunting, the pet trade and research through established permitting processes driven by appropriate laws and regulations. The aim of this study was to determine whether there is a trend in demand for regulated alien taxa based on permit requests and to ascertain the activities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Understanding crayfish impacts on specific ecosystem services is necessary not only for their regulation and management, but also to guard against detriment to human wellbeing in a continent where food security and water resources are already precarious (Egoh et al 2020). This is particularly relevant as some of the crayfish species were introduced for aquaculture and there are ongoing requests for the use of crayfishes, and indeed other species, in both inland fisheries and for aquaculture (Nunes, Zengeya, Measey et al 2017;Moshobane et al 2020). As economic information on fisheries and aquaculture development based on invasive crayfish is lacking, research into the factors driving the success, or failure, of such enterprises could provide important information for decision makers needing to consider economic and environmental factors in decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding crayfish impacts on specific ecosystem services is necessary not only for their regulation and management, but also to guard against detriment to human wellbeing in a continent where food security and water resources are already precarious (Egoh et al 2020). This is particularly relevant as some of the crayfish species were introduced for aquaculture and there are ongoing requests for the use of crayfishes, and indeed other species, in both inland fisheries and for aquaculture (Nunes, Zengeya, Measey et al 2017;Moshobane et al 2020). As economic information on fisheries and aquaculture development based on invasive crayfish is lacking, research into the factors driving the success, or failure, of such enterprises could provide important information for decision makers needing to consider economic and environmental factors in decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have profiled the nutritional value of O. ficus‐indica (Hernández‐Urbiola et al, 2011; Dahmardeh, 2012; Ö‐Zcan & al Juhaimi, 2011; Rocchetti et al, 2018; Sawaya et al, 1983); a more detailed review of the nutritional value of O. ficus‐indica is given by Cota‐Sánchez (2015). The usefulness of some exotic species can be explained by the ever‐growing demand for regulated species in South Africa and elsewhere (Moshobane et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant if the alien taxa in question meet the basic needs of remote communities and if important benefits such as poverty alleviation and food security result from the sale of these invasive speciesfor example, as firewood (Baiyegunhi, 2007;Barney et al, 2013;Makhado et al, 2016;Parker et al, 1999;Senyolo, 2016;Shackleton and Shackleton, n.d.;Shackleton et al, 2011;Shackleton et al, 2008b). A recent study by Moshobane et al (2020) showed that there is an increasing demand for useful alien species, particularly those that are regulated by law. There is thus a large gap in knowledge about the full extent of both the negative and the positive effects of useful alien species on ecosystem services and disservices (Vaz, Kueffer, Kull, Richardson, Schindler, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-native animals have been and continue to be introduced in South Africa through various pathways that include stowaways, biological control, scientific research, food, zoo and pet trade (Faulkner et al, 2020;Measey et al, 2020;Moshobane et al, 2020). The pet trade industry is growing in South Africa and includes several animal species from arthropods, amphibians, reptiles, fish, birds and mammals (Maligana et al, 2020;Moshobane et al, 2020;Nelufule et al, 2020;Shivambu et al, 2020aShivambu et al, , 2020bShivambu et al, , 2020cvan Wilgen et al, 2008). Some non-native species have established feral populations (i.e.…”
Section: Introductionmentioning
confidence: 99%